2014
DOI: 10.1242/jcs.152363
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of SQSTM1 with the motor protein dynein: SQSTM1 is required for normal dynein function and trafficking

Abstract: BSTRACTThe dynein motor protein complex is required for retrograde transport of vesicular cargo and for transport of aggregated proteins along microtubules for processing and degradation at perinuclear aggresomes. Disruption of this process leads to dysfunctional endosome accumulation and increased protein aggregation in the cell cytoplasm, both pathological features of neurodegenerative diseases. However, the exact mechanism of dynein functionality in these pathways is still being elucidated. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 88 publications
2
28
0
Order By: Relevance
“…In parallel, we determined whether metformin treatment might affect PLN stability in CMNCs, measured by 35 S-dependent metabolic labeling. Pulse-chase studies showed that the half-lives of wild-type PLN (τ = 9.5 ± 1.2 h) and R9C (τ = 8.8 ± 0.5 h) were similar in transduced CMNCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, we determined whether metformin treatment might affect PLN stability in CMNCs, measured by 35 S-dependent metabolic labeling. Pulse-chase studies showed that the half-lives of wild-type PLN (τ = 9.5 ± 1.2 h) and R9C (τ = 8.8 ± 0.5 h) were similar in transduced CMNCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HDAC6 is a cytosolic protein that plays a critical role in autophagosome-lysosome fusion; reduced HDAC6 levels are associated with stagnant autophagy and de novo protein aggregation (36). p62 interaction with HDAC6 and its recruitment to the microtubule organization center via dynein is important for dynein motor protein trafficking of ubiquitinylated proteins, as p62-null mouse embryonic fibroblasts become devoid of ubiquitin aggregates along microtubules (35). Taken together, these results can account for PLN translocation to the lysosomes after autophagosome biosynthesis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, SQSTM1, LC3‐II, and BAG3 have also been implicated in aggresome formation (Calderilla‐Barbosa et al., 2014) and were increased particularly in Cu OAC suggesting aggresome formation. In HT29, dynein, a retrograde transporter carrying aggregates to an aggresome, was increased on Cu OAC treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The increase in the autophagy adaptor proteins SQSTM1 and LC3-I/LC3-II did not correlate with a block in autophagy or with increased autophagy as there was no increase in autophagy structures (autolysosomes or early autophagic compartments). Indeed, SQSTM1, LC3-II, and BAG3 have also been implicated in aggresome formation (Calderilla-Barbosa et al, 2014) and were increased particularly in Cu OAC suggesting aggresome formation. In HT29, dynein, a retrograde transporter carrying aggregates to an aggresome, was increased on Cu OAC treatment.…”
Section: Discussionmentioning
confidence: 99%